Non-Extensive Aspects of Gluon Distribution and the Implications for QCD Phenomenology - Lucas S. Moriggi; Magno V. T. Machado (Physics)
This study presents new insights into gluon transverse momentum distributions through non-extensive statistical mechanics, addressing their implications for QCD phenomenology. The saturation physics and scaling laws present in high-energy collision data are investigated as a consequence of gluon distribution modification in a high-density regime. This analysis explores how these modifications influence observables across different collision systems, such as proton–proton, proton–nucleus, and relativistic heavy-ion collisions. Both particle high- and low-transverse-momentum regions are successfully described in hadron production.